The Relationship Between Post-Acne Scars and Quality of Life Among Medical Students of FK UNAND, Padang, Indonesia - Salsabila Aulia Kasbina; Satya Wydya Yenny; Hendra Permana; Aswiyanti Asri; Qaira Anum; Yulistini (International Journal of Public Health Excellence (IJPHE), 2026)
Post-acne scars are a condition of skin layer damage due to the healing process of acne vulgaris, causing the skin to appear depressed. This condition disrupts facial aesthetics and may become permanent, thereby affecting the patient’s psychological condition and quality of life. This study aimed to determine the relationship between the severity of post-acne scars and the quality of life among medical students of FK UNAND, Padang, Indonesia. This study was an analytic observational study with a cross-sectional design conducted from June to December 2023. The population consisted of medical students of FK UNAND batch 2020–2022 who had acne scars. The total sample was 88 respondents selected using consecutive sampling. Data were collected using the Facial Acne Scar Quality of Life (FASQOL) questionnaire and Dysmorphic Concern Questionnaire (DCQ). Statistical analysis was performed using One-Way ANOVA and Fisher’s Exact Test. The results showed that most respondents were female and aged 21 years. The majority experienced mild acne scars (46.6%). The mean FASQOL score was 14.11. Most respondents felt disturbed by the presence of acne scars on their face. The DCQ results showed that 88.6% of respondents had no dysmorphic disorder features. There was no significant relationship between acne scar severity and quality of life (p=0.938) nor dysmorphic disorder (p=0.241). The study concluded that there was no relationship between the severity of post-acne scars and the quality of life among medical students of FK UNAND, Padang, Indonesia